Analisis Faktor-Faktor yang Mempengaruhi Mahasiswa Akuntansi dalam Pemilihan Karir Menjadi Akuntan Publik (Studi empiris pada Perguruan Tinggi Negeri dan Swasta di Pekanbaru) - Yanti, Novri; Ratnawati, Vince; ', Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to examine the influence of the intrinsic value of work, financial rewards, work environment, professional recognition, social values, and personality labor market considerations in the selection of public accountant career.The samples in this study were students of existing state and private universities in Pekanbaru. Methods of data collection in this study is the method of questionnaire survey using instruments that are delivered directly to the students. Total Respondents were used in this analysis were 134 respondents (89%). Methods of Analysis is conducted with a multipleregression analysis using SPSS (Statistical Product and Service Solutions) Version 17.The results of testing hypotheses using the t test, concluded H2, H3, H4, H6 is accepted which has a significance value p-value <0.5, indicating that the variable financial reward, work environment, professional recognition, social values and labor market considerations have influence on the selection of public accountant career. While variable intrinsic value of work, social values and personality have a significance value of p-value > 0.5, H1, H5, H7 is not acceptable. The coefficient of determination in this study was 70%. These four variables affect the dependent variable by 70%, while 30% is influenced by other variables that are not addressed in this study.Keywords : Job Intrinsic Value, Financial Awards, Work Environment, Professional Recognition, Social Values, Job Market Considerations, Personality